2004
DOI: 10.1002/mrm.20117
|View full text |Cite
|
Sign up to set email alerts
|

Correction for gradient nonlinearity in continuously moving table MR imaging

Abstract: Recently, a number of methods have been demonstrated for large field of view MR imaging using continuous table motion. As with conventional, fixed-table MRI, the spatial encoding is performed using magnetic field gradients. However, it is demonstrated in this work that as a consequence of every measurement being made at a slightly different displacement between the object and the gradient field, gradient nonlinearities are manifest as blurring in addition to spatial distortion. Moreover, the blurring is spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…The technique is designed to reduce the distortion components from the z axis with no additional benefit in the axial plane. One angiography study using SMS 18 demonstrated additional distortion effects and blurring in all 3 imaging planes when utilising this acquisition technique. 105…”
Section: Introductionmentioning
confidence: 99%
“…The technique is designed to reduce the distortion components from the z axis with no additional benefit in the axial plane. One angiography study using SMS 18 demonstrated additional distortion effects and blurring in all 3 imaging planes when utilising this acquisition technique. 105…”
Section: Introductionmentioning
confidence: 99%
“…Here, averaging was performed in a weighted manner in hybrid k-space, reducing contrast variations due to gradient nonlinearity. In addition to averaging, the image quality can further be optimized by accurately correcting gradient nonlinearity (14). By implementing a gradient nonlinearity correction, a larger portion of the imaging FOV in the z-direction can be included in the data for reconstruction, thus decreasing necessary overlap of consecutive measurements and simultaneously increasing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, for incremental-FOV imaging with readout along the table direction, a significant cropping (i.e., a reduction in effective regional FOV length) may be necessary to make up for the inadequacy of existing methods for gradient nonlinearity effect correction. A recent study demonstrated improvements provided by the use of a new correction algorithm (12). Simulation studies and algorithm development are among our priorities for maximizing effective regional FOV (and hence scan efficiency) through advanced nonlinearity effect correction.…”
Section: Discussionmentioning
confidence: 99%